Blending in at the Cost of Losing Oneself: The Cyclical Relationship between Social Anxiety, Self-Disclosure, and Self-Uncertainty - Orr, Elizabeth (University of Waterloo, 2013)
Recent research has demonstrated that high social anxiety is associated with uncertainty about one’s self views and self-concept (Moscovitch et al., 2009; Stopa et al., 2010; Wilson & Rapee, 2006). However, no research has addressed potential mechanisms underlying the link between high social anxiety and low self-certainty nor has research examined whether this relationship is bi-directional. In the current research, I propose a cyclical model in which high social anxiety leads to low self-certainty, which in turn, feeds back into higher levels of social anxiety. I also propose that the relationship between high social anxiety and low self-certainty is mediated by the self-protective self-disclosure patterns employed by socially anxious individuals. In three interconnected studies, I examine the hypothesis that social anxiety, self-disclosure and self-certainty operate in a cyclical model. Study 1 provided a correlational test of the hypothesized feedback model in its entirety and demonstrated that honesty of self-disclosure was the most important and influential mechanism underlying the link between high social anxiety and low self-certainty. Experimentally manipulating the honesty of participants’ self-disclosures in Study 2 demonstrated that dishonest self-disclosures during a social task led to low self-certainty, but only amongst individuals high in trait performance anxiety. Finally, experimentally manipulating self-certainty in Study 3 demonstrated that low self-certainty led to high anticipatory anxiety about an upcoming self-disclosure task. Together, these results elucidate a cyclical maladaptive pattern in which low self-certainty as a result of self-protective self-disclosure leads to high social anxiety and a greater reluctance to self-disclose. Results from the three studies are discussed with respect to their theoretical implications and in relation to clinical applications for individuals with social anxiety disorder.
Keywords: Social Anxiety; Self-Certainty; Self-Disclosure; Psychology